Effect of hydrogen bonding on the liquid crystalline behavior of Poly(p-phenylene terephthamide) in sulfuric acid. (9th May 2018) - Zhou, Sheng; Li, Chang-Sheng; Fan, Xing-He; Shen, Zhihao
Abstract: Many factors affect the formation of lyotropic liquid crystals (LLCs) in the poly( p -phenylene terephthamide) (PPTA)/H2 SO4 system. In this systematic work, we prove that the hydrogen bonding between PPTA and H2 SO4 plays a very important role for the LLC formation by using a combination of several characterization methods. Texture features and transition temperatures of different phases owing to hydrogen bonding in the PPTA/H2 SO4 system were obtained by using polarized light microscopy and differential scanning calorimetry. 13 C NMR and FTIR spectroscopy were applied to investigate the chemical structures in different phases, especially the hydrogen bonding between PPTA and H2 SO4 . The effect of molecular weight on phase transition was also examined. Moreover, guest compounds such as H2 O, CH3 SO3 H, and carbon nanotube added will destroy the hydrogen-bonding network in the PPTA/H2 SO4 system, resulting in different phase behaviors. All these results demonstrate that hydrogen bonding between PPTA and H2 SO4 is the key factor for the highly ordered arrangement of polymer chains in the LLC state that is a nematic phase. Graphical abstract: Image 1 Highlights: A combination of PLM, DSC, FTIR, and NMR was used to study the effect of hydrogen bonding on LC behaviors of PPTA in H2 SO4 . The concentration and MW of PPTA, temperature, and addition of guest compounds all affect hydrogen bonding in the system. Hydrogen bonding is proved to be very important for the formation of the LLC phase of PPTA/H2 SO4 .